Analisis Ketersediaan Dan Asupa Zat Gizi Pada Menu Buka Puasa Pondok Pesantren Nurul Hakim - Nurul Kamila Paradisa; Reni Sofiyatin; Ni Ketut Sulendri; AASP Chandradewi (Jurnal Gizi Prima (Prime Nutrition Journal), 2019)
The 2013 Risekesdas data for short and thin 13th-15th adolescents inIndonesia is 35.5% and 11.1% and NTB is one of the provinces withmore than national travel. Nutritional problems attack all adolescentsincluding the boarding school teenagers. Fulfillment of nutrients isvery dependent on the organization of cottage meals. So that theavailability of nutrients in the cottage must meet the adequacy of thenutrition of students who can be seen from the menu provided,enough nutrients and varied every day is not lost in the Fastingmonth. The variety of materials used depends on the funds provided.The observation result is that the budget for the Nurul Hakimboarding school meal is IDR 250,000 / month with a less variedmenu. Researchers are interested in analyzing the availability withthe contribution of nutrients in the organization of the meal iftar.